Enhancing crystallization behavior for optimized performances of poly(TMC‐b‐(LLA‐ran‐GA)) by PDLA/PLLA stereocomplex crystallization. (7th March 2020) - Fan, Tiantang; Qin, Jingwen; Lin, Shengli; Ye, Wuyou; Liu, Qing; Fan, Zhongyong; Wang, Ye
Abstract : The blends of poly(1, 3‐trimethylene carbonate‐ b ‐(l ‐lactide‐ ran ‐glycolide)) (PTLG) with poly(d ‐lactide) (PDLA) were prepared via solution‐casting method using CH2 Cl2 as solvent. The poly(l ‐lactide) (PLLA) segments of PTLG with PDLA chain constructed as stereocomplex structures and growth stereocomplex crystals of PLA (sc‐PLA). The effects of sc‐PLA crystals on thermal behavior, mechanical properties, thermal decomposition of the PTLG/PDLA blends were investigated, respectively. The differential scanning calorimetry (DSC) and wide‐angle X‐ray diffraction (WAXD) results showed that the total crystallinity of the PTLG/PDLA blends was increased with the PDLA content increasing. Heterogeneous nucleation of sc‐PLA crystals induced crystallization of the PLLA segments in PTLG. The crystallization temperature of samples shifted to 107.5°C for the PTLG/PDLA‐20 blends compared with that of the PTLG matrix, and decreased the half‐time of crystallization. The mechanical measurement results indicated that the tensile strength of the PTLG/PDLA blends was improved from 21.1 MPa of the PTLG matrix to 39.5 MPa of PTLG/PDLA‐20 blends. The results of kinetics of thermal decomposition of the PTLG/PDLA blends by TGA showed that the apparent activation energy of the PTLG/PDLA blends was increased from 59.1 to 72.1 kJ/mol with the increasing of the PDLA content from 3 wt% to 20 wt%, which indicated the enhancement of thermal stability of the PTLG/PDLA blends by addition of PDLA. Furthermore, the biocompatibility of the PTLG/PDLA blends cultured with human adipose‐derived stem cells was evaluated by CCK‐8 and live/dead staining. The experiment results proved the PTLG/PDLA blends were a kind of biomaterial with excellent physical performances with very low cytotoxicity.